A benchmark model for financial markets - Eckhard Platen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
This paper introduces a benchmark model for financial markets, which is based on the unique characterization of a benchmark portfolio that is chosen to be the growth optimal portfolio. The general structure of risk premia for asset prices and portfolios is derived. Furthermore, the short rate is obtained as an average of appreciation rates. The benchmark model is shown to be locally arbitrage free, however, it still permits some form of arbitrage. Finally, a subclass of arbitrage free contingent claim prices is derived.
urn:nbn:de:kobv:11-10050040
Keywords: G10; G13; 330; financial market model; contingent claim pricing; benchmark model; growth optimal portfolio; arbitrage amount